Plant pathogen-induced volatiles attract parasitoids to increase parasitism of an insect vector - Martini, Xavier; Pelz-Stelinski, Kirsten S.; Stelinski, Lukasz L. (Frontiers in Ecology and Evolution, 2014)
Interactions between plant pathogens and arthropods have been predominantly studied through the prism of herbivorous arthropods. Currently, little is known about the effect of plant pathogens on the third trophic level. This question is particularly interesting in cases where pathogens manipulate host phenotype to increase vector attraction and presumably increase their own proliferation. Indeed, a predator or a parasitoid of a vector may take advantage of this manipulated phenotype to increase its foraging performance. We explored the case of a bacterial pathogen, Candidatus Liberibacter asiaticus (Las), which modifies the odors released by its host plant (citrus trees) to attract its vector, the psyllid Diaphorina citri. We found that the specialist parasitoid of D. citri, Tamarixia radiata, was attracted more toward Las-infected than uninfected plants. We demonstrated that this attractiveness was due to the release of methyl salicylate. Parasitization of D. citri nymphs on Las-infected plants was higher than on uninfected controls. Also, parasitization was higher on uninfected plants baited with methyl salicylate than on non-baited controls. This is the first report of a parasitoid “eavesdropping” on a plant volatile induced by bacterial pathogen infection, which also increases effectiveness of host seeking behavior of its herbivorous vector.